2020
DOI: 10.1007/s11255-020-02379-0
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume-to-lymphocyte ratio: a novel biomarker associated with overall survival in patients with nonmetastatic clear cell renal cell carcinoma treated with nephrectomy

Abstract: Introduction Renal cell carcinoma is a highly aggressive malignancy that causes significant morbidity and mortality. The rising number of newly diagnosed renal tumors results in a great need to search for new preoperative markers to evaluate the course of the disease and to help select patients who would benefit the most from additional postoperative care. The aim of our study was to evaluate the prognostic value of mean platelet volume-to-lymphocyte ratio (MPVLR) in patients undergoing nephrectomy for nonmeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…So far MPVLR has been widely studied in cardiovascular disease, and inflammatory response, but few in tumor prognosis. A recent study proved that high MPVLR (≥3.61) was independently associated with higher long-term overall mortality in nonmetastatic ccRCC patients ( 34 ). Our study was the first to investigate whether MPVLR was associated with the recurrence of patients with NMIBC.…”
Section: Discussionmentioning
confidence: 99%
“…So far MPVLR has been widely studied in cardiovascular disease, and inflammatory response, but few in tumor prognosis. A recent study proved that high MPVLR (≥3.61) was independently associated with higher long-term overall mortality in nonmetastatic ccRCC patients ( 34 ). Our study was the first to investigate whether MPVLR was associated with the recurrence of patients with NMIBC.…”
Section: Discussionmentioning
confidence: 99%
“… Życzkowski M et al, 64 Invasive breast cancer (IBC) High pre-treatment MPV level in IBC patients was a potential predictive factor. Gu M et al, 65 BC The combination of preoperative D-Dimer and MPV improves the predictive power of postoperative deep venous thrombosis risk in BC patients. Cui LN et al, 66 Breast cancer with bone metastases MPV can be used to predict the development of isolated bone metastases patients with breast cancer.…”
Section: Research Progress On the Mean Platelet Volume (Mpv) In Malignant Tumoursmentioning
confidence: 98%
“…Życzkowski M et al, 64 Invasive breast cancer (IBC) High pre-treatment MPV level in IBC patients was a potential predictive factor. Gu M et al, 65…”
Section: Rupa-matysekmentioning
confidence: 99%
“…We read the research study conducted by Zyczkowski et al [1] related with "Mean platelet volume-to-lymphocyte ratio: a novel biomarker associated with overall survival in patients with nonmetastatic clear cell renal cell carcinoma treated with nephrectomy" which was published in your journal, with great interest. This study's findings indicated that mean platelet volume-to-lymphocyte ratio (MPVLR) is an easily obtainable prognostic marker for overall survival in patients with nonmetastatic clear cell renal cell carcinoma treated with nephrectomy.…”
mentioning
confidence: 99%